2011
DOI: 10.1002/jbm.b.31914
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble argatroban for antithrombogenic surface coating of tissue‐engineered cardiovascular tissues

Abstract: Argatroban is a powerful synthetic anticoagulant, but due to its water-insoluble nature, it is unsuitable for use as a coating material to reduce the thrombogenic potential of natural or tissue-engineered blood-contacting cardiovascular tissues. On the other hand, anionic compounds could adsorb firmly onto connective tissues. Therefore, in this study, an anionic form of argatroban was prepared by neutralization from its alkaline solution, dialysis, and freeze-drying. The subsequently obtained argatroban deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Unlike heparin which indirectly inhibits thrombin, argatroban is characterized by fewer differences in efficacy among individuals. Several studies that implemented argatroban coatings on endovascular treatment devices have been reported . Imanishi et al developed balloon catheters coated with argatroban‐loaded hydrogel for the reduction of intimal hyperplasia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike heparin which indirectly inhibits thrombin, argatroban is characterized by fewer differences in efficacy among individuals. Several studies that implemented argatroban coatings on endovascular treatment devices have been reported . Imanishi et al developed balloon catheters coated with argatroban‐loaded hydrogel for the reduction of intimal hyperplasia .…”
Section: Discussionmentioning
confidence: 99%
“…Richey et al reported that argatroban particles could be ionically bound to the modified balloon surface, enabling the local delivery of high‐dose argatroban for a short time period . Argatroban‐coated stents have also been fabricated by immersing the stent grafts into an argatroban solution, with the stents exhibiting an in vivo antithrombotic effect for various time periods . Therefore, we used argatroban as an antithrombotic drug, and developed gelatin coated stents incorporating bFGF and argatroban.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we established a method involving argatroban loading prior to implantation to avoid graft thrombosis during the acute phase following implantation [23]. In the present study, argatroban loading was not performed prior to implantation because the diameter of the stent graft was considered to be sufficiently large and the velocity of the blood flow through the aorta is much higher than that of the peripheral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the lack of benefit is in the binding properties used and so other methods of binding heparin to device surfaces are being investigated (68)(69)(70). Additionally, direct thrombin inhibitors such as argatroban and bivalirudin could offer benefits (71)(72)(73) but no significant studies on efficacy are available.…”
Section: Surface Coatingmentioning
confidence: 99%
“…Pyrolytic carbon (55)(56)(57) Albumin (62) Heparin (65) Direct thrombin inhibitors (71)(72)(73) Sirolimus (74) SLIPs (77-81)…”
Section: Hydrophilic Polymersmentioning
confidence: 99%